2004
DOI: 10.1038/sj.onc.1207654
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor level controlled by a suppressor complex lost in an androgen-independent prostate cancer cell line

Abstract: Androgen receptor (AR) overexpression is one of the characteristics of prostate cancer (PC) that progresses to hormone independence. An androgen-independent (AI) derivative, with much higher AR-mRNA and protein levels than the parental LNCaP cell line, whose proliferation was androgen dependent (AD), was used to explore the mechanism of AR overexpression. We found that a suppressor element (ARS), previously identified in mouse AR and located in the 5 0 -untranslated region of human AR gene, malfunctions in AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 43 publications
4
54
0
Order By: Relevance
“…Therefore, inhibition of androgen receptor mRNA synthesis or stability contributes to the overall effect of LAQ824 on androgen receptor level. Consistent with this notion, the loss of an uncharacterized androgen receptor transcription suppressor was observed in a LNCaP-derived cell line that overexpresses androgen receptor (44). Expression of the androgen receptor suppressor complex could be partially induced by HDAC inhibitors (44).…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, inhibition of androgen receptor mRNA synthesis or stability contributes to the overall effect of LAQ824 on androgen receptor level. Consistent with this notion, the loss of an uncharacterized androgen receptor transcription suppressor was observed in a LNCaP-derived cell line that overexpresses androgen receptor (44). Expression of the androgen receptor suppressor complex could be partially induced by HDAC inhibitors (44).…”
Section: Discussionsupporting
confidence: 66%
“…Significantly, it has been found that this suppressor protein(s) could be induced to re-express in AI cells through histone deacetylase inhibitors, such as trichostatin A, sodium butyrate or suberoylanilide hydroxamic acid (SAHA). Consequently, a normal AR function was restored as indicated by regaining an androgen-dependent phenotype and apoptotic sensitivity to chemotherapeutic agents (24)(25)(26)(27). Consistent with these findings, histone deacetylase inhibitors LAQ824 and SAHA have also been reported to repress AR at both the transcriptional and posttranslational levels (28,29).…”
Section: Downregulation Of Ar Expression By Peitc Through Epigenetic supporting
confidence: 69%
“…We recently demonstrated that several genes, including p21, Bax, PSA and the AR suppressor (ARS) were repressed in androgenindependent but not in androgen-dependent cells. The silencing of PSA and ARS has been shown to be the likely result of CpG island methylation (25,27). The silencing of p21, Bax and ARS may also be associated with both the drug resistance of cancer cells to chemotherapeutic agents and the androgen-independent progression of the disease (25,27,47).…”
Section: Restoration Of Gstp1 Expression By Peitc Via Cpg Island Demementioning
confidence: 99%
See 2 more Smart Citations